Environmental data gaps in Black Sea catchment countries: INSPIRE and GEOSS State of Play. Issue 46 (February 2015) - Myroshnychenko, Volodymyr; Ray, Nicolas; Lehmann, Anthony; Giuliani, Gregory; Kideys, Ahmet; Weller, Philip; Teodor, Dan
Highlights: Large-scale gap analysis was performed on existing observation systems, networks, services and datasets for the Black Sea catchment. Gaps and areas are identified where further efforts are needed to reinforce existing observation systems. The question is addressed as to whether data sharing is sufficiently developed to meet the needs of environmental policies around the Black Sea. Abstract: This paper presents the results of a large analysis of environmental data gaps in countries of the Black Sea catchment performed in the context of the FP7 enviroGRIDS project in 2010. We also assessed the level of compatibility of the data to the European directive establishing an Infrastructure for Spatial Information in the European Community (INSPIRE) and to the international standards of data interoperability as advocated by the Group on Earth Observations (GEO) and implemented in the Global Earth Observation System of Systems (GEOSS). Many environmental datasets were analyzed at different scales (national, regional, European, and global) and the analysis revealed gaps in spatial and temporal environmental data coverage and problem of data compatibility at different scales. The analysis enabled the identification of areas where further efforts are needed to reinforce the existing observation systems in the region, such as monitoring systems to provide data on water quality in rivers, on the state of marine environments, or on pollution and nutrients loads from land based sources. A significant proportion of environmental datasets is not accessible or has limited access, so further efforts are needed to make them available to decision makers and scientists following the GEO data sharing principles. Compatibilities of many data sets and observation systems to international interoperability standards are low in this region, and we discuss what further efforts are needed to improve the situation and how this is relevant to environmental policies.